Turkey – Between Power and Vulnerability - Ralchev, Plamen (Research Papers, 2018)
The aim of this paper is to analyze the potential volatility of Turkey in result of internal transformation processes in the country and its “overstretch” with engagements abroad, especially the military operation on Syrian territory. Under the rule of President Erdogan Turkey began to play a more assertive role regionally. It positions itself not as a peripheral, Western-satellite state, but rather as a pivotal state with its own proper weight.In terms of methodology the paper employs case studies, comparative and critical analysis of economic and financial data from primary and secondary sources. The first part presents a political overview and assessment of Turkey’s foreign policy behavior and power claims. The second part focuses on Turkey’s economic problems and volatility prospects.